1992
DOI: 10.1172/jci115743
|View full text |Cite
|
Sign up to set email alerts
|

Ret oncogene activation in human thyroid neoplasms is restricted to the papillary cancer subtype.

Abstract: We have recently reported the activation of a new oncogene in human papillary thyroid carcinomas. This oncogene, papillary thyroid carcinoma (PTC), is a novel rearranged version of the ret tyrosine-kinase protooncogene. Thyroid neoplasms include a broad spectrum of malignant tumors, ranging from well-differentiated tumors to undifferentiated anaplastic carcinomas. To determine the frequency of ret oncogene activation, we analyzed 286 cases of human thyroid tumors of diverse histologic types. We found the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
192
2
6

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(205 citation statements)
references
References 19 publications
3
192
2
6
Order By: Relevance
“…The ret gene, located on Chromosome 10q, encodes a transmembrane tyrosine kinase receptor (13)(14)(15). Ret is normally expressed in neural crestderived cells; normal thyroid follicular epithelial cells do not express ret (19).…”
Section: Figure 2 Immunohistochemistry For Ck19mentioning
confidence: 99%
See 2 more Smart Citations
“…The ret gene, located on Chromosome 10q, encodes a transmembrane tyrosine kinase receptor (13)(14)(15). Ret is normally expressed in neural crestderived cells; normal thyroid follicular epithelial cells do not express ret (19).…”
Section: Figure 2 Immunohistochemistry For Ck19mentioning
confidence: 99%
“…However, in the majority of PCs, a gene rearrangement occurs that places the intracellular domain of the ret gene under the transcriptional control of one of several genes that are expressed in thyroid follicular epithelium (16). This chimeric gene, the ret/PTC oncogene, is specific to papillary carcinomas and encodes a protein product that contains the cytoplasmic portion of ret (13)(14)(15). Therefore, immunohistochemical detection of the carboxy terminus of the ret protein in thyroid follicular epithelial lesions serves as a reliable marker for papillary carcinoma (16).…”
Section: Figure 2 Immunohistochemistry For Ck19mentioning
confidence: 99%
See 1 more Smart Citation
“…Rearrangements of the ret protooncogene have been reported in a minority of PTC (Grieco et al, 1990;Santoro et al, 1992) in some studies, whereas another study demonstrated RET translocations in 59% of adult onset PTCs (Williams et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular alterations underlying the development of either PTC or FTC are poorly understood. Mutations in the ras proto-oncogene may represent an early event in follicular thyroid tumorigenesis (Lemoine et al, 1989;Suarez et al, 1990), while ret proto-oncogene rearrangements may be important in PTC (Grieco et al, 1990;Santoro et al, 1992, Williams et al, 1996. Unlike many common tumor types, mutations of p53 are seen infrequently in di erentiated thyroid cancer , though they are commonly present in anaplastic and poorly differentiated tumors (Ito et al, 1992).…”
Section: Introductionmentioning
confidence: 99%